JHU-083 selectively blocks glutaminase activity in brain CD11b+ cells and prevents depression-associated behaviors induced by chronic social defeat stress - Zhu, Xiaolei; Nedelcovych, Michael T; Thomas, Ajit G; Hasegawa, Yuto; Moreno-Megui, Aisa; Coomer, Wade; Vohra, Varun; Saito, Atsushi; Perez, Gabriel; Wu, Ying; Alt, Jesse; Prchalova, Eva; et al. (Neuropsychopharmacology, 2019)
There are a number of clinically effective treatments for stress-associated psychiatric diseases, including major depressive disorder (MDD). Nonetheless, many patients exhibit resistance to first-line interventions calling for novel interventions based on pathological mechanisms. Accumulating evidence implicates altered glutamate signaling in MDD pathophysiology, suggesting that modulation of glutamate signaling cascades may offer novel therapeutic potential. Here we report that JHU-083, our recently developed prodrug of the glutaminase inhibitor 6-diazo-5-oxo-L-norleucine (DON) ameliorates social avoidance and anhedonia-like behaviors in mice subjected to chronic social defeat stress (CSDS). JHU-083 normalized CSDS-induced increases in glutaminase activity specifically in microglia-enriched CD11b+ cells isolated from the prefrontal cortex and hippocampus. JHU-083 treatment also reverses the CSDS-induced inflammatory activation of CD11b+ cells. These results support the importance of altered glutamate signaling in the behavioral abnormalities observed in the CSDS model, and identify glutaminase in microglia-enriched CD11b+ cells as a pharmacotherapeutic target implicated in the pathophysiology of stress-associated psychiatric conditions such as MDD.
Keywords: Animals; Glutaminase; zánět; hipokampus; Prodrugs; CD11b Antigen; psychický stres; chování zvířat; Mice; Diazooxonorleucine; glutaminasa; signální transdukce; prekurzory léčiv; myši; Signal Transduction; prefrontální mozková kůra; Inflammation; Male; modely nemocí na zvířatech; Disease Models, Animal; Behavior, Animal; Hippocampus; deprese; zvířata; mužské pohlaví; Mice, Inbred C57BL; Depression; antigeny CD11b; Stress, Psychological; diazooxonorleucin; myši inbrední C57BL; Prefrontal Cortex